2015
DOI: 10.1159/000440835
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Linguistic Performance and Quality of Life in Healthy Aging

Abstract: Background/Aims: This study investigated quality of life (QoL) in relation to cognitive-linguistic performance and demographic characteristics (age, education and gender) in a large cohort of cognitively healthy older adults. Method: A total of 578 Greek-Cypriots aged 60-91 years were recruited from the Neurocognitive Study on Aging. Of those, 395 healthy participants (171 males and 224 females) who met all study criteria were retained. They completed measures of executive functioning, working memory, receptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
2
13
0
1
Order By: Relevance
“…Regarding verbal comprehension, no sex discrepancy in performance was found in a study that included auditory comprehension task, which was administered to a large cohort of healthy participants (Simos et al, 2014), similar results were obtained in another study focused on a verbal learning task (Constantinidou et al, 2014). Another study reported significantly higher scores for men in receptive vocabularyregardless of age, years of formal schooling and naming abilitybut similar performance across sexes for expressive vocabulary (Simos et al, 2011). Even though these studies include large samples with appropriate demographic characteristics such as a wide range of age and years of formal schooling, adequate representation of both sexes and recruitment from several geographic areas of Greece, making generalization of results is plausible, they do not provide any data on speech narratives.…”
Section: Introductionsupporting
confidence: 66%
“…Regarding verbal comprehension, no sex discrepancy in performance was found in a study that included auditory comprehension task, which was administered to a large cohort of healthy participants (Simos et al, 2014), similar results were obtained in another study focused on a verbal learning task (Constantinidou et al, 2014). Another study reported significantly higher scores for men in receptive vocabularyregardless of age, years of formal schooling and naming abilitybut similar performance across sexes for expressive vocabulary (Simos et al, 2011). Even though these studies include large samples with appropriate demographic characteristics such as a wide range of age and years of formal schooling, adequate representation of both sexes and recruitment from several geographic areas of Greece, making generalization of results is plausible, they do not provide any data on speech narratives.…”
Section: Introductionsupporting
confidence: 66%
“…Many other earlier studies have shown that gender, age, marital status, and educational level are related to QoL after stroke [6,7,8,9,11,12,13,14]. On the other hand, Constantinidou et al [33] found that gender and years of education affect several domains of QoL in healthy older adults.…”
Section: Discussionmentioning
confidence: 96%
“… 33 While most studies focusing on women showed no significant effects on quality of life, the DHEA concentration also did not affect the mortality in disabled women. 33 Recent studies have demonstrated a relationship between executive functioning, working memory, vocabulary measures, and both the physical and psychological health domains of the WHOQOL-BREF in healthy older adults, 35 suggesting that other neuropsychiatric systems, such as estrogen, that are related to cognition and quality of life in the female group. 36 …”
Section: Discussionmentioning
confidence: 99%